2011
DOI: 10.1002/ptr.3651
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Xanthatin from Xanthium strumarium Leaves

Abstract: The objective of the present work was to evaluate the biological activities of the major bioactive compound, xanthatin, and other compounds from Xanthium strumarium (Asteraceae) leaves. Inhibition of bloodstream forms of Trypanosoma brucei brucei and leukaemia HL-60 cell proliferation was assessed using resazurin as a vital stain. Xanthatin was found to be the major and most active compound against T. b. brucei with an IC(50) value of 2.63 µg/mL and a selectivity index of 20. The possible mode of action of xan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 44 publications
0
44
0
1
Order By: Relevance
“…Interestingly, other types of PCD were also reported when STLs were used against different pathogens. The STL xanthatin, which had good activity against Trypanosoma brucei brucei (IC 50 of 2.6 g/ml), triggered apoptosis in treated trypanosomes (38). Leishmania mexicana treated with 3 different STLs (helenalin, mexicanin, and dehydroleucodine) presented fragmented DNA, a hallmark of apoptosis-like death (14).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other types of PCD were also reported when STLs were used against different pathogens. The STL xanthatin, which had good activity against Trypanosoma brucei brucei (IC 50 of 2.6 g/ml), triggered apoptosis in treated trypanosomes (38). Leishmania mexicana treated with 3 different STLs (helenalin, mexicanin, and dehydroleucodine) presented fragmented DNA, a hallmark of apoptosis-like death (14).…”
Section: Discussionmentioning
confidence: 99%
“…Xanthatin (Figure 1), first isolated from cockleburs (Xanthium spp.) and characterized for its antimicrobial, anti-inflammatory, pro-apoptotic and trypanocidal properties [102,103], has been recovered from cultures of a strain of Paecilomyces sp. from Panax ginseng [104].…”
Section: Other Terpenoidsmentioning
confidence: 99%
“…Here, we focused on the biological effects of (-)-xanthatin on human breast cancer (MDA-MB-231 cells); however, experimental evidence that (-)-xanthatin has broad anti-proliferative effects coupled with cell death for different kinds of cancer cells is accumulating, such as human gastric carcinoma (MKN-45 cells) (Zhang et al, 2012a), human non-small-cell lung cancer (A549 cells) (Zhang et al, 2012b), and human leukemia (HL-60 cells) (Nibret et al, 2011). Taken together with these findings, it is suggested that (-)-xanthatin may be an intriguing chemical entity for inclusion with the other sesquiterpene lactones in future cancer clinical trials (Ghantous et al, 2010).…”
Section: Discussionmentioning
confidence: 99%